Pemacuan Pembungaan Tanaman Lengkeng (Euphoria longana Lam.) untuk Produksi Buah di Luar Musim - Theresia Prawitasari; Aris Munandar; Mursal Mursal (Fakultas Biologi | Universitas Jenderal Soedirman, 2007)
The objectives of this research were to analyze the effect of paclobutrazol and ethepon in substituting climate factors effect in flowering and fruiting processes of longan, to determine the application way and dozes of paclobutrazol, as well as the timing of ethepon application after paclobutrazol to stimulate ‘off-session’ longan fruiting. Three combined factors treatment namely: the way of paclobutrazol application (soil drench and foliar spray); dozes of paclobutrazol (control, 1 g, and 2 g paclobutrazol per tree); and the timing of ethepon application after paclobutrazol, were designed in randomized block design and applied at 20-30 years old longan trees, which were grouped into 3 group according to the amount of flushing twigs among all of the twigs in the whole canopy. Result of the research showed that specific climate conditions (2-3 months dry which was followed by temperature decrease until 15-22oC) as pre condition for the happening of natural flowering on longan might be substituted by paclobutrazol and ethepon. The application of 1 g paclobutrazol in foliar spray method, which was followed by application of 400 mg/l ethepon 1 month after paclobutrazol, might stimulated 20-30 years old longan trees, flowering 37.5 day after paclobutrazol application, while control trees did not flower until 120 days observation.The trees got foliar spray application way of paclobutrazol was induced after 29.8 DAPA, while the trees under soil drench were induced after 42.0 DAPA. Dozes 1 and 2 g paclobutrazol induced flowering after 15.9 and 16.9 DAPA, while control trees were induced after 74.8 DAPA. The fastest achieving time of the induction stage (17.7 DAPA) were shown in the trees under foliar spray application way of 1 g paclobutrazol which was followed by the application of 400 mg/l ethepon 1 month after paclobutrazol application (C2D1W1). Furthermore, the plants under the same treatment combination were differentiated faster (37.5 DAPA). The fastest induction and differentiation stage achieving time were strongly related to the highly of the leaf chlorophyll content (1.33 mg/l) as well as C/N ratio (9.67) which were the highest value in both of the variables. The average of the blossom achieving time was 52.3 DAPA. The differentiation and the blossom stage were shown only in the plants were in flushing condition, with 25-75% of flushing twigs. The decrease of twigs long addition parallel to the paclobutrazol dozes and vice versa to the ethepon application time. The faster the ethepon application time, the higher the twigs long addition. Finally, the result of the research showed that if the humidity of flowering and fruiting-plants canopy, as the result of paclobutrazol and ethepon application during the differentiation processes until ‘fruit set’ was keep protected, the retardant application in February (the middle of raining session in the research area) might supply longan fruits in June (the middle of dry session, when the longan fruits supply were very limited).